A patent review of Monoacylglycerol Lipase (MAGL) inhibitors (2013-2017). (2nd December 2017) - Granchi, Carlotta; Caligiuri, Isabella; Minutolo, Filippo; Rizzolio, Flavio; Tuccinardi, Tiziano
ABSTRACT: Introduction : Monoacylglycerol lipase is a serine hydrolase that plays a major role in the degradation of the endocannabinoid 2-arachidonoylglycerol. Because of this key role, selective inactivation of MAGL represents an interesting approach to obtain desirable effects in several diseases. Furthermore, MAGL is upregulated in cancer cells and primary tumors and its inhibition in aggressive breast, ovarian, and melanoma cancer cells impairs cell migration, invasiveness, and tumorigenicity. Areas covered : This review covers patent literature on MAGL inhibitors and their applications published from 2013 to 2017. Expert opinion : MAGL inhibition has gained considerable importance in many therapeutic fields and one compound has been subjected to Phase I studies. Even if a reasonable number of patents have been recently reported, novel MAGL inhibitors are still required, especially novel chemical classes displaying a reversible mechanism of action.